2016
DOI: 10.1016/j.molcel.2016.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ras/Raf/MEK/ERK Pathway Signaling by a Stress-Induced Phospho-Regulatory Circuit

Abstract: Summary Ras pathway signaling plays a critical role in cell growth control and is often upregulated in human cancer. The Raf kinases selectively interact with GTP-bound Ras and are important effectors of Ras signaling, functioning as the initiating kinases in the ERK cascade. Here, we identify a route for the phospho-inhibition of Ras/Raf/MEK/ERK pathway signaling that is mediated by the stress-activated JNK cascade. We find that key Ras pathway components, the RasGEF Sos1 and the Rafs, are phosphorylated on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 31 publications
6
70
2
Order By: Relevance
“…Recently, a small-molecule inhibitor, rigosertib, was shown to act as a RAS mimetic and interact with the RBDs of RAF kinases, RalGDS and PI3Ks, resulting in their inability to bind to activated RAS (Athuluri-Divakar et al, 2016). Recently, results from Ritt et al (2016) suggested a different mechanism on how rigosertib mediates its effects. The effects of rigosertib were seen to be largely indirect, mediated by the stress-induced phosphor-regulatory circuit that involves TNK cascade activation.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Recently, a small-molecule inhibitor, rigosertib, was shown to act as a RAS mimetic and interact with the RBDs of RAF kinases, RalGDS and PI3Ks, resulting in their inability to bind to activated RAS (Athuluri-Divakar et al, 2016). Recently, results from Ritt et al (2016) suggested a different mechanism on how rigosertib mediates its effects. The effects of rigosertib were seen to be largely indirect, mediated by the stress-induced phosphor-regulatory circuit that involves TNK cascade activation.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…In contrast to the ERK pathway, which primarily promotes cellular proliferation, JNK and p38 phosphorylate a range of substrates to promote inflammation and cell death (1,3). In addition, cross-regulation among the p38, JNK, and ERK pathways is important for the efficacy of various cancer therapies that are in use or in development (4,5). Molecular details on the more diverse upstream regulation of the p38 and JNK pathways are currently less clear, however.…”
mentioning
confidence: 99%
“…To further investigate whether signaling upstream of JNK1/2 is also influenced, we examined the activation of MAPK kinase (MEK), MKK3/6, MKK4, and MKK7, which activate downstream JNK1/2 . Notably, the HFD‐ or PA‐induced increase in phosphorylated MKK7, but not phosphorylated MEK, MKK3/6, or MKK4, was significantly inhibited by TPL2 deficiency, whereas TPL2 overexpression led to a further increase in MKK7 phosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 99%